Peran Guru dalam Mengembangkan Motorik Halus Mengayam Kertas pada Anak Kelompok B di TK Oikumene Kabupaten Sorong - Truince Limbir; Nurul Septia Wathani; Nursalim Nursalim (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
The purpose of this study was to determine the role of teachers in developing fine motor skills in paper weaving in Group B children at Oikumene Kindergarten, Sorong Regency. The research method used in this study was descriptive with a qualitative approach, namely data compiled in narrative and objective words. The results showed that children aged 5-6 years at Oikumene Kindergarten, Sorong Regency, engaged in several activities that can improve their fine motor skills, such as cutting, writing, weaving, shaping, folding, drawing, and so on. The results of the observations conducted by the researcher revealed that out of 15 children, 10 were in the Very Well Developed (BSB) indicator, while 4 children were in the Developing as Expected (BSH) indicator, and 1 child was in the Beginning to Develop (MB) indicator. According to the researcher's observations, the 1 child in the Beginning to Develop category was influenced by other factors, so the child remained in the Beginning to Develop indicator.